Investigating the Predictive Role of Parenting Styles and Parent-Child Relationship on Disruptive Mood Dysregulation Disorder - Khatoon Pourmaveddat; Zobeydeh dehghan manshadi (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2022)
Aim and Background: The disorder of mood disorders is one of the mood disorders recently introduced in childhood and adolescence and has a relatively high prevalence of childhood disorders. The present study investigated the role of parenting styles and parent-child relationships in predicting disruptive mood dysregulation disorder. Methods and Materials: This research is of descriptive-correlation type. The statistical population included all boy students aged 9 to 12 years with disruptive mood dysregulation disorder in Bushehr city (Iran) in 2017-2018. The sample consisted of 55 children with disruptive mood dysregulation disorder,selected by purposive sampling method, and 130 normal children with their parents, selected by a random cluster sampling method. Participants were assessed using a researcher-made anger and irritability questionnaire, the Alabama parenting questionnaire (APQ; Shelton, Frick, & Wootton, 1996), and The Pianta Child-Parent Relationship Scale (CPRS; Pianta, 1992). Research data were analyzed using correlation and logistic regression and SPSS-24 software. Findings: The logistic regression analysis showed that among different parenting styles, positive parenting dimensions and corporal punishment are stronger predictors of disruptive mood dysregulation disorder (p<0.01). Among the sub-scales of the parent-child relationship, conflict and general relationships are significant predictors of disruptive mood dysregulation disorder (p<0.01). Conclusions: According to the results, it can be concluded that positive parenting, corporal punishment, intimacy, conflict, and a generally positive relationship can predict disordered mood disorder, and one of the ways to reduce the disorder’s symptoms can be interventions. Be based on parental education.